Device parameters characterization with the use of EBIC - Oka Kurniawan (2010)
The performance of bipolar and photodiode devices is determined by the transport properties of the minority carriers, such as the minority carrier diffusion lengths and the surface recombination velocities. The Electron Beam Induced Current (EBIC) technique of the Scanning Electron Microscopy (SEM) has been widely used to characterize these two parameters. One of the most widely used methods involves a fitting process with the use of a fitting parameter called alpha. The accuracy of extracting the minority carrier diffusion lengths using this method is affected by several parameters, such as the surface recombination velocity and the exact locations of the edges of the depletion layer. Moreover, this method is only applicable when the p-n junction depth is assumed to be either very deep or very shallow. The present work aims to analyse the parameters affecting the accuracy, as well as to develop techniques to characterize diffusion lengths from a p-n junction that has a finite junction depth. The effect of the surface recombination velocities on the extraction of the diffusion lengths cornes from the fitting parameter, termed alpha, used in the rnethod. The present work analysed the factors affecting this alpha parameter and provided the required conditions for accurately determining the value of the surface recombination velocity. On the other hand, a technique to locate the edges of the depletion layer was developed. Thus, more accurate locations of the edges of the depletion layer can be obtained from the same measurement data used in extracting the diffusion lengths of the materials.